PROFIT MARGIN AND INVENTORY TURNOVER : HOW DO THEY AFFECT FINANCIAL DISTRESS IN RETAIL COMPANIES LISTED ON THE IDX 2019-2023 PERIOD IN THE ERA OF TECHNOLOGICAL DISRUPTION? - Inge Sulistyo; Hariyanto, Wiwit (Journal of Economic and Economic Policy, 2025)
Objective: This study aims to determine profit margin and inventory turnover on financial distress in retail companies that go public on the Indonesia Stock Exchange (IDX) in the era of technological disruption. Method: This study is a quantitative study with a population taken from retail companies listed on the Indonesia Stock Exchange (IDX) for the 2019 – 2023 period. The research sample was 14 companies that met the criteria using purposive sampling techniques. The data analysis technique used multiple linear regression with SPSS software ver 23. Results: Based on the results of the research that has been conducted, it shows that : (1) Profit margin have an effect on financial distress and (2) Inventory turnover have an effect on financial distress in retail companies listed on the Indonesia Stock Exchange in 2019-2023. Novelty: This study provides a novel insight by focusing on the impact of profit margin and inventory turnover on financial distress specifically in publicly listed retail companies during the era of technological disruption in Indonesia, a context that has been rarely explored in previous research.